Review of maternal mortality in a tertiary care urban teaching hospital: 10 year retrospective study - G., Shobha; Kanavi, Jayashree V.; Divater, Veena B.; Thomas, Annamma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objectives of this study were to calculate the maternal mortality ratio, causes for maternal death in our institution and the duration of hospital admission to death interval. Methods: The study included collecting and analyzing the details of maternal death in women who were admitted to St. Johns Medical College Hospital, Bengaluru, from January 2007 to December 2016. Results: Total maternal deaths were 61 and live births were 26,001 during the study period. The maternal mortality ratio (MMR) was 234.6 per 100,000 live births. Majority of maternal deaths occurred in women aged 18 - 35 years 56 (91.80%) women, primipara 45 (73.77%) and referred cases to our institution from other hospitals 52 (85.24%). Most of the women died in the postnatal period 54 (88.52%). Direct obstetric causes accounted for 44 (72.13%) maternal deaths and indirect causes 17 (27.86%) deaths. Preeclampsia and eclampsia were the leading causes for death 13 (21.31%) followed by acute fatty liver of pregnancy 12 (19.67%), hemorrhage 7 (13.11%) and sepsis 6 (9.83%). Anemia was present in 77.04% of women at the time of admission to our hospital. Thirty six (59.01%) women died within a week of admission to the hospital, in which 13 (21.31%) women died in less than 24hours of admission. Twenty five (40.98%) women died after a week of admission to hospital. Conclusions: Apart from the triad of preeclampsia, obstetric haemorrhage and sepsis, acute fatty liver of pregnancy has emerged as an important cause of maternal death. Most of the maternal deaths are preventable. Early detection of complications and timely referral to tertiary care hospital in St. Johns Medical College Hospital, Bengaluru, Karnataka, India decreases maternal morbidity and mortality.